2016
DOI: 10.1098/rspb.2016.0721
|View full text |Cite
|
Sign up to set email alerts
|

Immigration of susceptible hosts triggers the evolution of alternative parasite defence strategies

Abstract: Migration of hosts and parasites can have a profound impact on host-parasite ecological and evolutionary interactions. Using the bacterium Pseudomonas aeruginosa UCBPP-PA14 and its phage DMS3vir, we here show that immigration of naive hosts into coevolving populations of hosts and parasites can influence the mechanistic basis underlying host defence evolution. Specifically, we found that at high levels of bacterial immigration, bacteria switched from clustered regularly interspaced short palindromic repeats (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 42 publications
8
35
0
Order By: Relevance
“…In this context, the key question is when CRISPR-Cas is favoured over alternative defence strategies [32]. Experimental, theoretical and correlational studies have suggested a role for viral abundance and diversity [27,28,33,34], direct and indirect fitness costs of CRISPR-Cas immune systems (e.g. autoimmunity, reduced horizontal gene transfer, induced fitness costs, see §1c below) [35 -38] and epistasis with other host genes [39,40].…”
Section: (B) Ecology and Diversity Of Crispr-cas Immunitymentioning
confidence: 99%
“…In this context, the key question is when CRISPR-Cas is favoured over alternative defence strategies [32]. Experimental, theoretical and correlational studies have suggested a role for viral abundance and diversity [27,28,33,34], direct and indirect fitness costs of CRISPR-Cas immune systems (e.g. autoimmunity, reduced horizontal gene transfer, induced fitness costs, see §1c below) [35 -38] and epistasis with other host genes [39,40].…”
Section: (B) Ecology and Diversity Of Crispr-cas Immunitymentioning
confidence: 99%
“…How phage can persist in the face of this extremely adaptable immune system remains unclear. Previous theoretical and limited experimental work has explained persistence by invoking spatial hetereogeneity [34,69], negative frequency-dependent selection [61], and host switching to a constitutive defense strategy such as surface receptor modification [70,71].…”
Section: A Case Study: Crispr-phage Coevolutionmentioning
confidence: 99%
“…Processed CRISPR transcripts guide Cas proteins to detect and destroy reinfecting phage that carry the cognate target sequence [12,13]. Phage can in turn overcome CRISPR-based immunity by acquiring a point mutation in the target sequence on their genome [14], although the emergence and spread of such phage "escape" mutants is constrained by both the diversity of CRISPR immunity alleles in the bacterial population and the fitness costs associated with the phage mutations [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%